Precision metagenomics sequencing for food safety: hybrid assembly of Shiga toxin-producing Escherichia coli in enriched agricultural water - Maguire, Meghan; Ramachandran, Padmini; Tallent, Sandra; Mammel, Mark K.; Brown, Eric W.; Allard, Marc W.; Musser, Steven M.; González-Escalona, Narjol (Frontiers in Microbiology, 2023)
Culture-independent metagenomic sequencing of enriched agricultural water could expedite detection and virulotyping of Shiga toxin-producing Escherichia coli (STEC). We previously determined the limit of assembly of a complete closed and fragmented metagenome-assembled genome (MAG) for O157:H7 in enriched agricultural water using long reads (Oxford Nanopore) was 107 and 105 CFU/ml, respectively. However, the nanopore assemblies did not have enough accuracy to be used in SNP phylogenies and cannot be used for precise identification of an outbreak STEC strain. The aim of this study was to determine the limits of detection and assembly for STECs in enriched agricultural water by Illumina MiSeq sequencing technology alone, followed by establishing the limit of hybrid assembly with nanopore long read sequencing using three different hybrid assemblers (SPAdes, Unicycler, and OPERA-MS). We aimed to generate a genome with enough accuracy to be used in a SNP phylogeny. Classification of the MiSeq and nanopore sequencing identified the same highly abundant species. Using the totality of the MiSeq output and a precision metagenomics approach in which the E. coli reads are binned prior to assembly, the limit of detection and assembly of STECs by MiSeq was determined to be 105 CFU/ml and 107 CFU/ml, respectively. While a complete, closed MAG could not be generated at any concentration, a complete, fragmented MAG was produced using the SPAdes assembler with an STEC concentration of at least 107 CFU/ml. At this concentration, hybrid assembled-contigs aligned to the nanopore-assembled genome could be accurately placed in a neighbor joining tree. The MiSeq limit of detection and assembly is less sensitive than nanopore sequencing, likely due factors including the small starting material (50ng vs 1ug) and the dilution of the library loaded on the cartridge. This pilot study demonstrates that MiSeq sequencing requires higher coverage in precision metagenomic samples; however, with